An approach to make statistical forecasting of products with stationary/seasonal patterns (2014)
At any company there are hundreds, maybe thousands of products that must be forecasted with the best accuracy, in order to make a good demand management process, which are required at all planning levels in a company -- Statistical forecasting must be done fast and sometimes there are not enough resources to do it well -- In In this paper we make a proposal of an approach to define the parameter of the exponential smoothing model for products with a behavior pattern stationary or seasonal/stationary in the historical data, to obtain “good forecasting" A numerical example is used to show the effectiveness of the proposed method